PENGEMBANGAN LKPD IPA BERBASIS INKUIRI TERBIMBING PADA MATERI OPTIK UNTUK PESERTA DIDIK KELAS VIII - Nurul Fadhilatunnisa; Nur Kuswanti; Noer Af’idah (Discovery, 2021)
Developing science student worksheet based on Guided Inquiry optical objectfor grade eight was a general purpose of this study. The specific purposes were todescribe the process of developing science student worksheet based on Guided Inquiryand its feasibility based on its validity. The development model used in this study was ADDIEthat consiseds analysis, design, development, implementation, and evaluation. However, theimplementation phase was not carried out due to a pandemic. The research questionnaremethod was a method used in the data collection process in this study. This developmentresearch resulted in a product in the form of a science student worksheet based on GuidedInquiry optical object for grade eight. The results of this development research indicatethat the Science Student Worksheet Based on Guided Inquiry Optical Subject for GradeEigth included in the very valid category because it obtained a validity scor of 3.79.